EVALUASI FORMULASI SEDIAAN KRIM BODY SCRUB DARI AMPAS KELAPA (Cocos nucifera L) - Solihah, Riyadatus; Ze'roh, Halimatus (JURNAL MEDICAL P-ISSN : 2685-7960 e-ISSN : 2685-7979, 2023)
. One of the plants that can be used is coconut pulp which is the product of coconut fruit waste (Cocos nucifera L). The purpose of this study is to determine the characteristics of coconut pulp raw materials (Cocos nucifera L) in body scrub cream preparations. The research method used was quantitative with an experimental research design by making a body scrub cream from coconut pulp with the concentration of coconut pulp used was 10g, 15g, and 20g. Data analysis used a one-way anova statistical test. The results obtained in the organoleptical test obtained all preparations have a rough texture, brownish white color, fresh smell, semi-solid shape. In the homogeneity test all preparations are homogeneous. In the pH test, all pH preparations were in the range of 7 in accordance with the pH standard, namely 4.5-8. The spreadability test shows that the three formulations have values ranging from 6 cm where the standard spreadability of cream preparations is 5-7 cm, for the one-way ANOVA statistical test shows p < 0.05 which means there is a significant difference between all formulations. The adhesion test shows that the three formulations have an adhesion test value ranging from 4-5 seconds where the adhesion has a standard that is> 1 second, for the one-way ANOVA statistical test shows p < 0.05, which means there is a significant difference between all formulations. Suggestions for researchers are that further research needs to be carried out by combining coconut pulp with other ingredients.